Study the Factors Affecting the Funding Management of the Mutual Funds of the Board Directors of Nan District, Luang Prabang Province - XIONG, Mee; HOONGSENGPHA, Soudthida; INDAVONG, Dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aims to study the management factors that impact on the operation of the management committee responsible for the mutual aid fund of Nan district, Luang Prabang Province, this study was used a questionnaire as a tool to collect the data and was used 265 forms, with a confidence value of 0.977 and IOC value was higher than 0.83. The statistics were used multiple regression analysis with a statistical significance level of 0.05. The management factors include 7 factors, including: 1. Fund planning (X1), 2. fund structure (X2), 3. personnel and employees performing duties (X3), 4. supervision and leadership (X4), 5. Coordination (X5), 6. performance reporting (X6) and 7. budget management (X7) were analyzed to find relationships that affect the operations of the fund management board, which include 4 aspects: 1. Fund goals (Y1), 2. internal management systems and processes (Y2), 3. Resources (Y3) and 4. member satisfaction (Y4). From the results found that: All 7 management factors were correlated with (Y1) and (Y2) are at a medium level, while (Y3) and (Y4) were low correlation, and the overall of 7 management factors were found 3 factors with a significance at 0.01, which included: 1. Guidance-leadership, 2. coordination, and 3. budget management. Therefore, it can be said that for some management factors that do not affect to the operational success of the board of directors responsible for the fund, which is a result of the management of some factors not being implemented as well as they should be, they should be improved and corrected. Although there are some factors that affect the operation of the board of directors, they are still at a moderate level.